Reducing Ruminal Ammonia Production With Improvement in Feed Utilization Efficiency and Performance of Murrah Buffalo (Bubalus bubalis) Through Dietary Supplementation of Plant-Based Feed Additive Blend - Chanu, Yendrembam Mery; Paul, Shyam Sundar; Dey, Avijit; Dahiya, Satbir Singh (Frontiers in Veterinary Science, 2020)
The study evaluated potential of blends of eucalyptus oil and aqueous extract of mulethi (root of Glycyrrhiza glabra) to reduce rate of ruminal ammonia production without affecting feed digestion to improve nitrogen utilization efficiency and performance of Murrah buffalo (Bubalus bubalis). Based on preliminary independent studies with graded doses of eucalyptus oil and mulethi root aqueous extract in modulating in vitro rumen fermentation, four blends of feed additive comprising of graded doses (5,10,15, 25 µL) of eucalyptus oil and a fixed quantity (15 µL) of aqueous extract of mulethi roots were prepared and examined for their effects on in vitro rumen fermentation, methane and gas production in 100 mL calibrated glass syringes by standard IVGP protocol. Rumen liquor was collected from four rumen fistulated Murrah buffaloes fed a total mixed ration. Out of four blends, blend-1 comprising of 5 µL eucalyptus oil and 15 µL aqueous extract (233.6 g / L DW) of mulethi per 40 mL in vitro medium was found to reduce ammonia production significantly (P<0.001) without affecting feed digestibility. An equivalent dose of blend-1 (10.5 mL eucalyptus oil and 7.35 g mulethi root powder/h/d) fed to four rumen fistulated buffaloes for twenty four days resulted in 50% reduction (P<0.05) in rumen ammonia level with no inhibition in feed fermentation or short chain fatty acids production. The total bacterial population including Ruminococcus albus, Fibrobacter succinogenes, Butyrivibrio fibrisolvens and Megasphaera elsdenii as well as anaerobic fungi and methanogenic archaea remained unaffected (P>0.05). Twelve buffalo calves (avg. BW 137.5± 9.2 kg, 8-12 months old) divided into two groups of six each and fed a total mixed ration (concentrate: roughage; 60:40) with or without supplementation of blend-1 for about 3 months demonstrated 14% increase (P<0.05) in average daily gain in BW with a trend (p<0.10) in improvement of feed or protein utilization efficiency (1.4 vs 1.1 g CP/g ADG; 21.4% increase). Thus, supplementation of eucalyptus oil- mulethi root blend could reduce ruminal ammonia production and improve feed utilization efficiency in ruminants.